2012
DOI: 10.1093/jrr/rrs079
|View full text |Cite
|
Sign up to set email alerts
|

Relative biological effects of neutron mixed-beam irradiation for boron neutron capture therapy on cell survival and DNA double-strand breaks in cultured mammalian cells

Abstract: Understanding the biological effects of neutron mixed-beam irradiation used for boron neutron capture therapy (BNCT) is important in order to improve the efficacy of the therapy and to reduce side effects. In the present study, cell viability and DNA double-strand breaks (DNA-DSBs) were examined in Chinese hamster ovary cells (CHO-K1) and their radiosensitive mutant cells (xrs5, Ku80-deficient), following neutron mixed-beam irradiation for BNCT. Cell viability was significantly impaired in the neutron irradiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…Compared to X-rays (LDR), the SF was significantly decreased after irradiation with monoenergetic neutrons (0.56 MeV, 1.2 MeV). This effectiveness of 0.56 MeV neutrons on the clonogenic survival confirms the results of Okumura et al [ 34 ]. Frankenberg-Schwager et al [ 22 ] obtained an RBE of 5.4 for a different cell line, experimental conditions and reference radiation quality.…”
Section: Discussionsupporting
confidence: 90%
“…Compared to X-rays (LDR), the SF was significantly decreased after irradiation with monoenergetic neutrons (0.56 MeV, 1.2 MeV). This effectiveness of 0.56 MeV neutrons on the clonogenic survival confirms the results of Okumura et al [ 34 ]. Frankenberg-Schwager et al [ 22 ] obtained an RBE of 5.4 for a different cell line, experimental conditions and reference radiation quality.…”
Section: Discussionsupporting
confidence: 90%
“…Previously, we reported that the 53BP1 foci induced by neutron irradiation were closer to each other and had different spatial distributions from those induced by gamma rays (10). These characteristics of 53BP1 foci are indicative of clustered DNA DSBs (10,11). In this study, we found that fractionated neutron irradiation induced larger foci than did gamma irradiation.…”
Section: Discussionsupporting
confidence: 57%
“…Similar findings were made by Asaithamby et al (2008) who reported lower maximum numbers of foci after exposure of human skin fibroblasts to either iron ions (150 and 236 keV/mm), silicon ions (44 keV/mm), oxygen ions (14 keV/mm) compared to g-rays. Okumura et al (2013) further detected similar numbers of p53 binding protein 1(53BP1) foci, known to colocalize with gH2AX foci (Lassmann et al 2010), after exposing hamster ovary cells to a mixed neutron beam and g-rays (i.e., RBE about 1). Importantly, to date no studies have been reported on the yield of gH2AX foci after exposure of human lymphocytes to high energy neutrons.…”
Section: Repair Kinetics Of Gh2ax Focimentioning
confidence: 88%
“…Therefore, it is possible that closely spaced individual foci cluster together and consequently make clear discrimination of individual foci difficult (Rübe et al 2011). Otherwise, discrimination of closely spaced and/or overlapping foci can also be limited by the optical resolution of the microscope system and lead to an underestimation of actual foci numbers (Okumura et al 2013).…”
Section: Repair Kinetics Of Gh2ax Focimentioning
confidence: 99%